Cynthia L. Haven, Evolution of Desire. A Life of René Girard, Michigan State University Press, East Lansing 2018, s. 317. - Romejko, Adam (Studia Gdańskie, 2019)
Cynthia L. Haven, Evolution of Desire. A Life of René Girard, Michigan State University Press, East Lansing 2018, s. 317.